(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Tsvetkova G. G. Тhe modern characteristic of the professional improvement of teachers of humanitarian specialities. The essential features of self-development of the teachers of humanitarian disciplines are characterized; a comparative analysis of the peculiarities of the professional improvement of the teachers of humanitarian disciplines and the teachers of comprehensive schools is made, the reasons for the success of self-development of teachers of humanitarian disciplines are distinguished in the article. It is proved that the formation of national motives of professional activity of a professional of the high school is a reflexive and changing process of reaching new horizons in the professional activities, assignment of the hierarchy of motives, values, affecting the development of a professional specialist.